Differential Responses of Human Dendritic Cells to Live or Inactivated Staphylococcus aureus: Impact on Cytokine Production and T Helper Expansion - Cruciani, Melania; Sandini, Silvia; Etna, Marilena P.; Giacomini, Elena; Camilli, Romina; Severa, Martina; Rizzo, Fabiana; Bagnoli, Fabio; Hiscott, John; Coccia, Eliana M. (Frontiers in Immunology, 2019)
Understanding Staphylococcus aureus (S. aureus)-host immune system interaction is crucial to meet the tremendous medical need associated with this life-threatening bacterial infection. Given the crucial role of dendritic cells (DC) in dictating immune responses upon microbial challenge, we investigated how the bacterial viability and the conservation of structural integrity influence the response of human DC to S. aureus. To this end, human primary DC were stimulated with the methicillin resistant S. aureus USA300 live strain, USA300 inactivated by heat (HI), ultraviolet irradiation (UVI) or paraformaldehyde treatment (PFAI) and subsequently analyzed for cell phenotype and immune-modulatory properties. Although no differences in terms of DC viability and maturation were observed when DC were stimulated with live or inactivated bacteria, the production of IL-12, IL-23 and pro-inflammatory cytokines differed significantly and, as a result, the Th1 and Th17 polarization was more pronounced in response to live versus inactivated S. aureus. Interestingly, cytokine production in DC treated with live and inactivated USA300 required phagocytosis, whereas blocking Toll-like receptor signaling mainly reduced the cytokine release by live and HI USA300. A further analysis of IFN-β signaling revealed the induction of a cGAS-STING-independent and IRF3-dependent signaling pathway(s) in UVI-stimulated DC. This study underscores the capacity of human DC to discriminate between live and inactivated S. aureus and, further, indicates that DC may represent a valuable experimental setting to test different inactivation methods with regard to the retention of S. aureus immunoregulatory properties. These and further insights may be useful for the development of novel therapeutic and prophylactic anti S. aureus vaccine strategies.